Fast Charge Transfer Kinetics Enabled by Carbon‐Coated, Heterostructured SnO2/SnSx Arrays for Robust, Flexible Lithium‐Ion Batteries. Issue 2 (22nd January 2022) - Xue, Lichun; Chen, Feiming; Zhang, Zhenbao; Gao, Yang; Chen, Dengjie
Abstract: Tin (Sn)‐based materials possessing high theoretical capacity have shown great potential for next‐generation lithium‐ion batteries (NGLIBs). Its poor conductivity and severe volume expansion, however, hinder practical applications. Herein, we prepare flexible carbon cloth supported SnO2 /SnSx heterostructured arrays coated with carbon (SnO2 /SnSx @C) with an easy hydrothermal process and carbonization. The resulting SnO2 /SnSx @C electrode is capable of providing high capacity, good rate capability, and long‐term stability. Specifically, SnO2 /SnSx @C shows an initial discharge specific capacity of 1898.7 mAh g −1 with Coulombic efficiency of 77.5 % and retains 1047.5 mAh g −1 after 100 cycles at 0.2 A g −1 . The superior electrochemical performance of SnO2 /SnSx @C is attributed to the well‐established unique structure: (1) the carbon cloth offers a flexible framework that can enhance the integrity of nanostructures and facilitate charge transfer; (2) both experimental and theoretical studies demonstrate that the SnO2 /SnSx heterostructure can speed up charge transfer, and this heterostructure as a buffer framework can also mitigate expansion in volume; and (3) carbon arrays are beneficial for preventing the SnO2 /SnSx electrode from pulverization and enhancing charge transfer. Our findings clearly indicate that Sn‐based heterostructures are promising for high‐capacity and stable NGLIBs. Abstract : Heterostructures : The SnO2 /SnSx @C electrode, which is supported on flexible carbon cloth, covered with in situ carbon, and especially benefits from the SnO2 /SnSx heterostructured arrays, has demonstrated high capacity, good rate capability, and long‐term stability for lithium‐ion batteries. The enhanced electrochemical performance is due to the accelerated charge transfer kinetics, the integrity of nanostructures, the mitigated volume expansion, and the prevention of pulverization.